2008
DOI: 10.1093/jac/dkn103
|View full text |Cite
|
Sign up to set email alerts
|

Long-term (4 years) efficacy of lopinavir/ritonavir monotherapy for maintenance of HIV suppression

Abstract: Our data support the long-term efficacy and safety of lopinavir/ritonavir monotherapy for the maintenance of HIV suppression, a finding that must be confirmed in larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 6 publications
1
22
0
1
Order By: Relevance
“…The emergence of protease mutations occurred late, between W40 and W90, at a low level of viremia but after several weeks of almost continuous viral replication. It is important that intermittent viremia (an HIV-1 RNA load of more than 50 but less than 500 copies/ ml) was evident in a higher proportion of patients in the LPV/r monotherapy arm than in the triple-combination arm (3), not only in this study of antiretroviral-naïve patients but also in maintenance studies of patients with previously fully suppressed viral loads (1,2,18). However, patients with advanced infections, high viral loads (above 100,000 copies/ml), and low CD4 cell counts (below 100 cells/mm 3 ) were excluded from this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of protease mutations occurred late, between W40 and W90, at a low level of viremia but after several weeks of almost continuous viral replication. It is important that intermittent viremia (an HIV-1 RNA load of more than 50 but less than 500 copies/ ml) was evident in a higher proportion of patients in the LPV/r monotherapy arm than in the triple-combination arm (3), not only in this study of antiretroviral-naïve patients but also in maintenance studies of patients with previously fully suppressed viral loads (1,2,18). However, patients with advanced infections, high viral loads (above 100,000 copies/ml), and low CD4 cell counts (below 100 cells/mm 3 ) were excluded from this study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, combination therapy with LPV/r rarely selects for PI resistance in antiretroviral-naïve patients (13). The prevalences of PI resistance during single-drug maintenance therapy with LPV/r in the previously mentioned randomized studies were comparable to those observed during LPV/r-based triple therapy, with the selection of major PI resistance mutations such as M46I, V82A, and L90M (1,2,18). In the first 48 weeks of the MONARK study, resistance mutations in the HIV protease gene were detected in 3 (3.6%) of 83 patients receiving LPV/r monotherapy and resistance mutations in the HIV reverse transcriptase gene were detected in 1 of 53 patients receiving LPV/r triple therapy (3).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…This probably could be attributed to inefficient metabolism caused by the SNP 1461_1462insA (rs rs67666821) in the CYP3A4 gene, which encodes a protein that has no functional activity (presence of the SNP \ 0.06 % in White subjects), and the contribution of other SNPs in the genes of proteins involved in drug ADME processes [27,30].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the Malawian setting with high-level NRTI resistance, virologic suppression rates were 70% overall and exceeded 85% among survivors at the end of 1 year on second-line therapy [22]; long-term follow-up of this cohort has not yet been reported. Such favorable response is likely due to the potency of boosted protease inhibitors that have shown substantial activity among protease inhibitor-naïve patients, even as monotherapy [34][35][36][37]. Alternatively, residual NRTI activity even in the setting of mutations may be sufficient to contribute to virological suppression [38,39].…”
Section: Resistance Implications Of Monitoring Strategiesmentioning
confidence: 99%